Development of Active PV Array Using Real-Time Scanning Method. Issue 1 (June 2021) - Itako, K; Xu, C; Kudoh, T; Koh, K; Ge, Q
Abstract: This paper presents a novel control strategy for active photovoltaic (APV) array using real-time scanning method. This proposed technology reduces extreme power drops due to the partial shading conditions (PSCs). In this paper, PSIM software is used to simulate the conventional photovoltaic (PV) array and the newly proposed APV array. The comparative analysis results show that this newly proposed technology can effectively reduce the power loss caused by the PSCs to the PV generation system. Assuming a practical system, we will verify the practicality of the proposed system by conducting a demonstration experiment with a large array scale. We also built a monitor system to monitor the generated power of each unit.